Epigenetic analysis leads to identification of HNF1B as a subtype-specific susceptibility gene for ovarian cancer - Shen, H.; Fridley, B.L.; Song, H.L.; Lawrenson, K.; Cunningham, J.M.; Ramus, S.J.; Cicek, M.S.; Tyrer, J.; Stram, D.; Larson, M.C.; Kobel, M.; Ziogas, A.; et al. (2013)
HNF1B is overexpressed in clear cell epithelial ovarian cancer, and we observed epigenetic silencing in serous epithelial ovarian cancer, leading us to hypothesize that variation in this gene differentially associates with epithelial ovarian cancer risk according to histological subtype. Here we comprehensively map variation in HNF1B with respect to epithelial ovarian cancer risk and analyse DNA methylation and expression profiles across histological subtypes. Different single-nucleotide polymorphisms associate with invasive serous (rs7405776 odds ratio (OR) = 1.13, P = 3.1 x 10(-10)) and clear cell (rs11651755 OR = 0.77, P = 1.6 x 10(-8)) epithelial ovarian cancer. Risk alleles for the serous subtype associate with higher HNF1B-promoter methylation in these tumours. Unmethylated, expressed HNF1B, primarily present in clear cell tumours, coincides with a CpG island methylator phenotype affecting numerous other promoters throughout the genome. Different variants in HNF1B associate with risk of serous and clear cell epithelial ovarian cancer; DNA methylation and expression patterns are also notably distinct between these subtypes. These findings underscore distinct mechanisms driving different epithelial ovarian cancer histological subtypes.